Maslahah-Based Institutional Mediation in Civil Servant Divorce: The Role of the Personnel Development Division at the Lampung High Prosecutor’s Office - Saputra, Joni; Grafizha, Achmad Baqiy (Universitas Islam Negeri Raden Intan Lampung, 2026)
The divorce process of State Civil Apparatus (ASN) at the Lampung High Prosecutor’s Office faces an institutional problem marked by administrative dominance, absence of a time limit for mediation, and lack of technical guidelines ensuring certainty, fairness, and psychological protection for the parties. This study aims to analyse how the Personnel Development Division resolves ASN divorce cases and formulate an effective, benefit-oriented development-mediation model. The theoretical framework is maslahah mursalah, which positions family integrity, employees’ private rights, procedural certainty, and institutional stability as core considerations. This research is empirical legal field research conducted at the Lampung High Prosecutor’s Office, supported by library research, using juridical-empirical and conceptual approaches. Data were obtained through observation of development practices, interviews with Division officers, documentation of regulations and procedural files, and literature on family and civil service law. The data were analysed qualitatively through reduction, thematic categorisation, interpretation, and assessment based on maslahah mursalah principles. The findings show that the Division plays a significant role in examining applications, summoning the parties, providing marital development, and facilitating mediation. However, this function remains suboptimal because mediation still depends heavily on the parties’ attendance and openness, lacks a clear time standard, and has not been handled by assigned competent mediators. The study recommends technical mediation procedures, institutional guidelines, a maximum thirty-day mediation period, certified mediators, and preventive programs such as marital counselling, education on spousal rights and obligations, and family communication training.